Addressing adverse synergies between chemical and biological pollutants at schools—The ‘SynAir-G’ hypothesis - Papadopoulos, Nikolaos G.; Akdis, Cezmi; Akdis, Mubeccel; Damialis, Athanasios; Esposito, Giuseppina; Fergadiotou, Ioana; Goroncy, Christian; Guitton, Pierre; Gotua, Maia; Erotokritou, Kleanthis; Jartti, Tuomas; Murray, Clare; et al. (Allergy, 2023)
While the number and types of indoor air pollutants is rising, much is suspected but little is known about the impact of their potentially synergistic interactions, upon human health. Gases, particulate matter, organic compounds but also allergens and viruses, fall within the ‘pollutant’ definition. Distinct populations, such as children and allergy and asthma sufferers are highly susceptible, while a low socioeconomic background is a further susceptibility factor; however, no specific guidance is available. We spend most of our time indoors; for children, the school environment is of paramount importance and potentially amenable to intervention. The interactions between some pollutant classes have been studied. However, a lot is missing with respect to understanding interactions between specific pollutants of different classes in terms of concentrations, timing and sequence, to improve targeting and upgrade standards. SynAir-G is a European Commission-funded project aiming to reveal and quantify synergistic interactions between different pollutants affecting health, from mechanisms to real life, focusing on the school setting. It will develop a comprehensive and responsive multipollutant monitoring system, advance environmentally friendly interventions, and disseminate the generated knowledge to relevant stakeholders in accessible and actionable formats. The aim of this article it to put forward the SynAir-G hypothesis, and describe its background and objectives.
CRIS-Team Scopus Importer:2023-09-08
Keywords: aerobiology; allergy; artificial intelligence; asthma; biosensors; children; school; virus; volatile organic compounds